The Draft Genome of the Non-Host-Associated Methanobrevibacter arboriphilus Strain DH1 Encodes a Large Repertoire of Adhesin-Like Proteins - Poehlein, Anja (Archaea, 2017)
Methanobrevibacter arboriphilus strain DH1 is an autotrophic methanogen that was isolated from the wetwood of methane-emitting trees. This species has been of considerable interest for its unusual oxygen tolerance and has been studied as a model organism for more than four decades. Strain DH1 is closely related to other host-associated Methanobrevibacter species from intestinal tracts of animals and the rumen, making this strain an interesting candidate for comparative analysis to identify factors important for colonizing intestinal environments. Here, the genome sequence of M. arboriphilus strain DH1 is reported. The draft genome is composed of 2.445.031 bp with an average GC content of 25.44% and predicted to harbour 1964 protein-encoding genes. Among the predicted genes, there are also more than 50 putative genes for the so-called adhesin-like proteins (ALPs). The presence of ALP-encoding genes in the genome of this non-host-associated methanogen strongly suggests that target surfaces for ALPs other than host tissues also need to be considered as potential interaction partners. The high abundance of ALPs may also indicate that these types of proteins are more characteristic for specific phylogenetic groups of methanogens rather than being indicative for a particular environment the methanogens thrives in.